Forest Gaps Modulate the Composition and Co-Occurrence Network of Soil Bacterial Community in Larix principis-rupprechtii Mayr Plantation - Yajie Niu; Wenjun Liang; Xi Wei; Youzhi Han (Agronomy, 2022)
Forest gaps create a favorable microenvironment for the growth of the soil microbial community. This study aimed to explore the effects of gap-related microenvironmental heterogeneity on soil bacterial communities in Larix principis-rupprechtii Mayr forest gaps. Therefore, the redundancy analysis (RDA) and structure equations modeling (SEM) of affecting elements were further used to test the significance of forest gaps’ effect on soil bacterial community composition and co-occurrence structure complexity. The formation of forest gaps increased canopy opening (CO) and significantly increased soil moisture content (SW), soil temperature (ST) and the accumulation of acid phosphatase (PHO) and sucrase (INV) in the soil, and the G250 (forest gap size: >250 m2) was most conductive to the accumulation of light and soil total nutrient. G50, G70, and G100 (forest gap size: 50–70 m2, 70–100 m2, 100–125 m2) were most favorable for the natural regeneration of the L. principis-rupprechtii Mayr plantation. The light properties under the forest gaps were the most significant factor that influenced the soil bacterial community composition, followed by the size of the forest gap, with standard path coefficients (Std. PCs) of 0.45 and −0.37, respectively. The canopy opening (CO), relative light intensity (RLA) and leaf area index (LAI) were considered to be the most important environmental factors affecting bacterial community composition (Std. PCs: 0.97, 0.99, and −0.93, respectively). The natural regeneration density under the forest gap was the most significant factor influencing the complexity of the soil bacterial community co-occurrence network, followed by soil nutrients (Std. PCs: 0.87 and −0.76, respectively).